Why the IMF and OECD are Wrong about Inequality and Growth - Clemens Fuest; Florian Neumeier; Daniel Stöhlker (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
In recent studies the IMF and the OECD claim that inequality has a negative impact on economic growth and conclude that redistribution policies have no adverse growth effects. We argue that this claim is misleading. We show that, for developed countries, the correlation between inequality and growth is positive, not negative. But this correlation cannot be given a causal interpretation.
Keywords: 330